PENGARUH LATIHAN SENAM AEROBIK TERHADAP KEMAMPUAN MOTORIK SISWI SMK NEGERI 4 PADANG - Nurjanah, Efa; Putra, Yogi Arnaldo; Padli; Mia, Anisa Sholiha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of aerobic exercise on the motor skills of female students at SMK Negeri 4 Padang. The study used a quasi-experimental approach with a One Group Pretest–Posttest Design, referring to Mawarda and Nurhidayat (2021). The study population consisted of 17 female students, while a sample of 10 students was selected using purposive sampling. These students were students who had previously actively participated in extracurricular aerobic exercise activities. Motor skills were measured using the Barrow Motor Ability Test, which included the Standing Broad Jump, Softball Throw, Zigzag Run, Wall Pass, Medicine Ball Put, and 60-Yard Dash. Data were analyzed using the Shapiro–Wilk normality test and paired t-test. The results showed that the average total motor ability T-score increased from 300.00 ± 20.83 in the pretest to 322.21 ± 18.37 in the posttest after participating in 16 aerobic exercise sessions. The results of the hypothesis test showed a calculated t-value of 2.964, which was greater than the t-table value of 2.262 at a significance level of α = 0.05 (df = 9), thus the hypothesis was accepted. Thus, it can be concluded that aerobic exercise significantly improved the motor skills of female students at SMK Negeri 4 Padang